Biomedical applications of silk and its role for intervertebral disc repair. Issue 4 (6th October 2022) - Croft, Andreas S.; Spessot, Eugenia; Bhattacharjee, Promita; Yang, Yuejiao; Motta, Antonella; Wöltje, Michael; Gantenbein, Benjamin
Abstract: Intervertebral disc (IVD) degeneration (IDD) is the main contributor to chronic low back pain. To date, the present therapies mainly focus on treating the symptoms caused by IDD rather than addressing the problem itself. For this reason, researchers have searched for a suitable biomaterial to repair and/or regenerate the IVD. A promising candidate to fill this gap is silk, which has already been used as a biomaterial for many years. Therefore, this review aims first to elaborate on the different origins from which silk is harvested, the individual composition, and the characteristics of each silk type. Another goal is to enlighten why silk is so suitable as a biomaterial, discuss its functionalization, and how it could be used for tissue engineering purposes. The second part of this review aims to provide an overview of preclinical studies using silk‐based biomaterials to repair the inner region of the IVD, the nucleus pulposus (NP), and the IVD's outer area, the annulus fibrosus (AF). Since the NP and the AF differ fundamentally in their structure, different therapeutic approaches are required. Consequently, silk‐containing hydrogels have been used mainly to repair the NP, and silk‐based scaffolds have been used for the AF. Although most preclinical studies have shown promising results in IVD‐related repair and regeneration, their clinical transition is yet to come. Abstract : For years, researchers have been seeking a suitable biomaterial to repair and/or regenerate the intervertebral disc (IVD) and a promising candidate to fill this gap could be the application of silk. Therefore, this review aims to elaborate on the different origins from which silk is harvested, the characteristics of each silk type and how it can be used for tissue engineering purposes. Moreover, the review provides an overview of preclinical studies that have used silk‐based biomaterials to repair the inner region of the IVD, the nucleus pulposus, as well as the IVD's outer region, the annulus fibrosus.